2019
DOI: 10.1111/jcmm.14700
|View full text |Cite
|
Sign up to set email alerts
|

Asperpyrone A attenuates RANKL‐induced osteoclast formation through inhibiting NFATc1, Ca2+ signalling and oxidative stress

Abstract: Imbalance of osteoblast and osteoclast in adult leads to a variety of bone‐related diseases, including osteoporosis. Thus, suppressing the activity of osteoclastic bone resorption becomes the main therapeutic strategy for osteoporosis. Asperpyrone A is a natural compound isolated from Aspergillus niger with various biological activities of antitumour, antimicrobial and antioxidant. The present study was designed to investigate the effects of Asperpyrone A on osteoclastogenesis and to explore its underlining me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…BMMs were seeded in plates (96-well plate) at a concentration of 8×10 3 cells per well and cultured in a-MEM (Thermo Fisher Scientific, CA, USA) supplemented with 50 ng/ml M-CSF (R&D Systems, MN, USA) overnight according to the method published by Jin and Chen in 2019 (7,26). After adherence, the BMMs were stimulated with GST-rRANKL (50 ng/ml) (R&D Systems, MN, USA), and peiminine (Feiyubio, Jiangsu, China, CAS no.…”
Section: Evaluation Of Peiminine Efficacy and Toxicitymentioning
confidence: 99%
“…BMMs were seeded in plates (96-well plate) at a concentration of 8×10 3 cells per well and cultured in a-MEM (Thermo Fisher Scientific, CA, USA) supplemented with 50 ng/ml M-CSF (R&D Systems, MN, USA) overnight according to the method published by Jin and Chen in 2019 (7,26). After adherence, the BMMs were stimulated with GST-rRANKL (50 ng/ml) (R&D Systems, MN, USA), and peiminine (Feiyubio, Jiangsu, China, CAS no.…”
Section: Evaluation Of Peiminine Efficacy and Toxicitymentioning
confidence: 99%
“…Although these drugs showed inhibitory effect on osteoclast activity, they had no effect on osteogenic activity. [14][15][16] Simply reducing osteoclast activity may interfere with bone formation, reduce bone transformation and bring side effects such as mandibular osteonecrosis. Studies have shown that the proliferation of early osteoclasts requires the activation of β-catenin; however, the activated β-catenin inhibits the differentiation of osteoclasts.…”
mentioning
confidence: 99%
“…Therefore, alternative therapeutic agents to prevent osteolytic diseases are urgent to be exploited. Many herbs have been proved possessing the effects to treat osteoporosis ( Chen et al, 2019 ; Jin et al, 2019 ). RH, an important stilbene-type component extracted from the root of Rheum undulatum L. , possesses various biological activities, such as anti-allergic, anti-cancer, anti-diabetic and anti-inflammatory activities in the previous reports (A.…”
Section: Discussionmentioning
confidence: 99%